الجدارات الوظيفية اللازمة للقيادات الأكاديمية بالجامعات المصرية: تصور مقترح - محمد، عبدالناصر محمد رشاد; عباس، هشام سيد (الجمعية المصرية للتربية المقارنة والإدارة التعليمية, 2020)
حاول البحث التعرف على الجدارات الوظيفية اللازمة للقيادات الأكاديمية بالجامعات المصرية وقد استخدم البحث المنهج الوصفي؛ باعتباره أكثر المناهج الملائمة لوصف الإطار النظري من خلال عرض الأسس النظرية ذات العلاقة بالجدارات الوظيفية للقيادات الأكاديمية بالجامعات، وعليه يتناول نشأة الجدارات وأهميتها، وخصائص الجدارات الوظيفية، وأنواع الجدارات الوظيفية ومجالاتها، وعرض التحديات الثلاثة المتعلقة بتدويل التعليم الجامعي، والعولمة، والتنافسية، ورصد واقع اختيار القيادات الأكاديمية بالجامعات المصرية وطرق اختيارهم وفقا لقانون تنظيم الجامعات رقم 49 لسنة 1972 وتعديلاته، وبرامج تنمية القيادات الأكاديمية بالجامعات المصرية مهنيا، واستطلاع رأى الخبراء حول الجدارات الوظيفية المشتركة للقيادات الأكاديمية بالجامعات المصرية وعددهم اثنين وعشرين أستاذا روعي في اختيارهم ثلاثة اعتبارات أساسية، وهى التخصص، وشغل الوظائف القيادية الأكاديمية الجامعية، والمشاركة في أنشطة الجودة والتطوير ذات العلاقة بالقيادات الأكاديمية، والجدارات اللازمة لها. وتوصل البحث إلي وضع تصور مقترح انطلق من نوعين من المنطلقات هما: المنطلقات النظرية والتي تمثلت في طيعة التحديات العالمية التي تواجه الجامعات، والاهتمام بتفعيل عملية اختيار القيادات الأكاديمية باعتبارهم الأصول الحقيقية للجامعة، والتطور في متطلبات شغل وظائف القيادات من الكفايات إلى الجدارات، أما المنطلقات المحلية فتتمثل في التعديلات المتلاحقة التي طرأت على قانون تنظيم الجامعات بشان شغل الوظائف القيادية، واعتبار مشروع تنمية قدرات أعضاء هيئة التدريس والقيادات كأحد المشروعات القومية لتطوير التعليم العالي في مصر، ثم عرض التصور المقترح لعدد من الجدارات الوظيفية المشتركة اللازمة لاختيار القيادات الأكاديمية وتتمثل في جدارات خاصة بالتفكير الاستراتيجي مثل التعاون مع الأطراف المعنية في صياغة رؤية واضحة لمستقبل الكلية والجامعة، وربط أولويات العمل لدى المرؤوسين بالأهداف الاستراتيجية للجامعة، وجدارات الإنجاز وهى تهتم بالمهام اكثر من التأثير في الأخرين مثل البحث عن الفرص الأفضل لتحقيق التنافسية المحلية والعالمية للجامعة وتشجيع أعضاء هيئة التدريس على التطوير والابتكار في أبحاثهم العلمية، أما الجدارات المتعلقة بالحزم التقنية فتتمثل في امتلاك القدرة على توظيف شبكات المعلومات والتعامل مع البرمجيات وتوظيف البيانات والوسائط التكنولوجية في صنع القرار التعليمي الجامعي، أما الجدارات الخاصة بالحزم الشخصية السلوكية فهي تتعلق باهتمام القائد بالتأثير في الأخرين مثل الحزم في مواجهة المرؤوسين بأسباب تدنى أدائهم وتحفيزهم، وامتلاك مهارة الاستماع والتعامل مع التكتلات غير الرسمية، وتنمية مشاعر الولاء والانتماء المؤسسي لدى العاملين، والجدارات الخاصة بالمساعدات والخدمات الإنسانية والمتعلقة بالاستجابة لاحتياجات أعضاء هيئة التدريس والعاملين والطلاب من خلال الأصغاء لهم وتفهم أفكارهم، وتلبية احتياجاتهم وحل مشكلاتهم والتواصل معهم وتوثيق العلاقات الإنسانية معهم، أما جدارات الفعالية الشخصية والمتعلقة بالتعامل مع الصعوبات والضغوط المباشرة كالثبات الانفعالي في مواجهة الأزمات، وتذليل العقبات التي تعوق أعضاء هيئة التدريس عن أداء عملهم، والتمسك بتطبيق القرارات الصعبة.
research Try to know: What are the job competencies necessary for academic leaders in Egyptian universities, The research used the descriptive approach, as it is the most appropriate approach to describe the theoretical framework by presenting theoretical foundations related to the functional competencies of academic leaders in universities, and it deals with the emergence and importance of competencies, the characteristics of functional competencies, types of functional competencies and its fields, and the presentation of the three challenges related to the internationalization of university education and globalization, competitiveness, and monitoring the reality of the selection of academic leaders in Egyptian universities and the methods of their selection according to the Law of Universities Regulation No. 49 of 1972, and programs of developing academic leaders in Egyptian universities professionally, and knowing the opinions of The experts considered the functional competencies of the academic leaders in the Egyptian universities, and the twenty-two professors took into account their choice of three basic considerations, specialization, filling the academic leadership positions, and participating in the quality activities related to the academic leaders. The research reached to develop a suggested proposal launched from two types of premises: theoretical premises that were represented in the obedience of global challenges facing universities, interesting in activating the process of selecting academic leaders as considered real premises of the university, and the development in the requirements of occupying leadership positions from competencies to competencies, as for the local premises, It is represented in the successive amendments that occurred in the law of regulating universities regarding occupying leadership positions, and considering the project of developing the capabilities of faculty members and leaderships as one of the national projects to develop higher education in Egypt, and then presented the suggested proposal for a number of The common functional competencies necessary for selecting academic leaders are represented in competencies specific to strategic thinking, such as cooperation with the stakeholders concerned in formulating a clear vision for the future of the faculty and university. and linking the work priorities of the principals to the university's strategic goals, and the accomplishment care about tasks more than influencing others, such as searching for the best opportunities to achieve the local and global competitiveness of the university and encouraging faculty members to develop and innovate in their scientific research, while the competencies related to technical packages are represented in having the ability to Employing information networks, dealing with software, and employing data and technological media in university educational decision making. As for the competencies of behavioral personal packages, they relate to the leader’s interest in influencing others, such as packages in Confronting subordinates with reasons for their poor performance and motivation, having the skill of listening and dealing with informal blocs, developing feelings of loyalty and institutional affiliation with workers, and the competencies of humanitarian assistance and services related to responding to the needs of faculty, workers, and students by listening to them, understanding their ideas, meeting their needs, solving their problems, and communicating with them and documenting human relations with them, as for the efficacy and personal efficacy of dealing with difficulties and direct pressures such as emotional stability in facing crises, and overcoming obstacles that hinder members of the training body Reyes reported doing their work, and sticking to hard decisions.
Keywords: الإدارة التعليمية -- التعليم العالي -- القيادات الأكاديمية -- مصر